Highlights of research on overland flow for advanced treatment of wastewater : final report - Lee, Charles R., author.; Waterways Experiment Station (U.S.); Cold Regions Research and Engineering Laboratory (U.S.) (Vicksburg, Miss. : Dept. of Defense, Dept. of the Army, Corps of Engineers, Waterways Experiment Station, Environmental Effects Laboratory, 1976)
Issued November 1976. Prepared for U.S. Army Cold Regions Research and Engineering Laboratory, Hanover, N.H. Cover title. Includes bibliographical references (pages 21-22). Mode of access: Internet.